English for international journalists - Gandon, Mike, ....-; Purdey, Heather, ....- (London ; New York : Routledge, 2013)
English for International Journalists is a clear and engaging step-by-step guide for non-native speakers using English in journalism across all forms of media. In-depth language analysis is provided in the specialised context of journalism, as well as a comprehensive approach to the rules and guidelines necessary for avoiding the pitfalls and errors that undermine accuracy and clarity. The book, written by Mike Gandon and edited by Heather Purdey, covers a broad range of vital subjects, including: * Making contact * Interviewing * Grammar and journalistic writing * Sensitive issues * The language of argument * The language of impartial and accurate reporting * Bloggers and broadcasters * Reporting economy, health and the environment. The book is closely supported by online resources concentrating on the spoken word, intonation and pronunciation, and also features an expansive range of exercises and tests, suitable for self-study or to be set as coursework. English for International Journalists presents readers with the essential tools for producing journalism in English today.
Includes index.
Keywords: English language -- Textbooks for foreign speakers; English language -- Grammar; English language -- Usage; Journalism -- Authorship